Essentials of Sports Nutrition and Supplements - Antonio, Jose; Kalman, Douglas; Stout, Jeffrey R.; Greenwood, Mike; Willoughby, Darryn S.; Haff, G. Gregory (Humana Press : Imprint: Humana, 2008)
Millions of consumers want to lose body fat, gain muscle mass, and/or improve exercise performance. In addition to an exercise program, they often look to sports supplements as 'tools' to help them reach their goals. This book, the culmination of years of work by the thought leaders in the sports nutrition field will help the consumer, student, scientist, and sports nutrition professional sift through the huge volume of information and come up with reasonable and scientifically-based ideas and conclusions about sports nutrition. Written and edited by the leaders in the field and members of the International Society of Sports Nutrition, the Essentials of Sports Nutrition and Supplements combines basic science with the best in applied sports nutrition. Topics in this book include: Endocrinology and Exercise Principles of Exercise Training An Overview of Dietary Supplements Nutritional Needs of Endurance Athletes Nutritional Needs of Strength-Power Athletes Sports Application of Creatine Eating to Improve Body Composition Pre-, During, and Post-Workout Nutrition for Endurance Athletes Pre- During, and Post-Workout Nutrition for Strength-Power Athletes But the book covers much more than the short list above. Whether you are a student, scientist or sports nutrition professional, this book will serve as the resource for you in this rapidly growing field.